Research on JiTT Based on Mobile Internet (Asian Education Studies, 2016)
JiTT is a kind of new teaching mode which is supported by information technology, promoting students' learning participation and effective teaching. The development of mobile Internet and the popularity of BYOD provide a new impetus for JiTT. On the basis of discussing the connotation and implementation process of JiTT, this paper analyzes the advantages and characteristics of using mobile network to support JiTT. Combined with the characteristics of mobile network technology and JiTT which involves two stage teaching and three key issues, the JiTT model based on mobile network was constructed. Finally, taking "animation programming foundation" as an example, JiTT was designed and carried out by supporting of Moso teach. Research shows that the proposed JiTT model based on mobile network is feasible, and the mobile network provides a strong support for effective preview, feedback and active learning.